Mesoscale phenomena and their contribution to the global response: a focus on the magnetotail transition region and magnetosphere-ionosphere coupling - Gabrielse, Christine; Gkioulidou, Matina; Merkin, Slava; Malaspina, David; Turner, Drew L.; Chen, Margaret W.; Ohtani, Shin-ichi; Nishimura, Yukitoshi; Liu, Jiang; Birn, Joachim; Deng, Yue; Runov, Andrei; et al. (Frontiers in Astronomy and Space Sciences, 2023)
An important question that is being increasingly studied across subdisciplines of Heliophysics is “how do mesoscale phenomena contribute to the global response of the system?” This review paper focuses on this question within two specific but interlinked regions in Near-Earth space: the magnetotail’s transition region to the inner magnetosphere and the ionosphere. There is a concerted effort within the Geospace Environment Modeling (GEM) community to understand the degree to which mesoscale transport in the magnetotail contributes to the global dynamics of magnetic flux transport and dipolarization, particle transport and injections contributing to the storm-time ring current development, and the substorm current wedge. Because the magnetosphere-ionosphere is a tightly coupled system, it is also important to understand how mesoscale transport in the magnetotail impacts auroral precipitation and the global ionospheric system response. Groups within the Coupling, Energetics and Dynamics of Atmospheric Regions Program (CEDAR) community have also been studying how the ionosphere-thermosphere responds to these mesoscale drivers. These specific open questions are part of a larger need to better characterize and quantify mesoscale “messengers” or “conduits” of information—magnetic flux, particle flux, current, and energy—which are key to understanding the global system. After reviewing recent progress and open questions, we suggest datasets that, if developed in the future, will help answer these questions.